In Silico Study of Chemical Compounds in Plantago major L. as Anti-Androgen - Baihaqi, Achmad Al; Isman, Hasna Siti Munifah; Fauziyyah, Ganis Fitria; Hutabarat, Rismauli Ruth Natasari; Hartono, Adi; Megantara, Sandra (Indonesian Society for Cancer Chemoprevention, 2022)
Prostate cancer is the most common type of cancer diagnosed in men worldwide and the second leading cause of death after lung cancer. Testosterone and dihydrotestosterone (DHT) have been known to play an essential role in prostate cancer. Androgen receptor (AR) binding to the ligand allows homodimerization and translocation to the nucleus, which acts as a transcription factor for androgen-responsive genes such as PSA (Prostate-specific antigen). Although many anti-androgens have been established, including Bicalutamide, Flutamide, and Abiraterone, the problem of non-specific cytotoxicity effects and cancer recurrence due to potential drug resistance remains a significant obstacle to establishing effective therapy. Plantago major L. is one of the plants that can choose anticancer therapy because, based on reports, it has anticancer activity through DNA damage in cancer cells. This study focused on the search for the potential phytochemical activity of Plantago major L. as an anti-androgen, non-cytotoxic, and had significant AR inhibitory activity. This study uses Lipinski prediction (RO5), ADMET prediction, and a structure-based approach with molecular docking techniques using the PDB ID 2AM9 receptor structure and 13 compounds from Plantago major L. as test ligands compared to known AR antagonists. From the research results, Hispidulin has the highest potential as an anti-androgen with binding energy (-9.43 kcal/mol) that is closest to natural ligands and is smaller than Flutamide as a comparison drug. This anti-androgen activity was hypothesized from the similarity of hydrogen bonds with amino acid residues 705-Asn and 711-Gln as key AR residues present in Hispidulin.Keywords: Prostate cancer, Androgen Receptor, Plantago major L., ADMET, In Silico.